Analysis of the stability of 3Y-TZP zirconia abutments after thermocycling and mechanical loading - Almeida, Paulo J. (2016)
Objectives: Although implant abutments made of yttria-stabilized tetragonal zirconia poly crystal (3Y-TZP) show great predictability, some issues related to its aging require further study. The objective of this in vitro study is to assess the stability of 3Y-TZP zirconia implant abutments with two different implant connections when subjected to aging simulation through thermocycling and mechanical loading (TCML).Methods: Ten 3Y-TZP zirconia abutments were selected and equally divided into two groups (n = 5): CEZr, abutments for externally hexed implants; and CIZr, abutments for implants with an internal conical connection. The samples were subjected to thermocycling (5000 cycles; 5-55 C) and mechanical loading (1.2 x 106 cycles; 88.8 N; 4 Hz). Before and after the aging procedures, X-ray diffraction (XRD) analysis was conducted to observe tetragonal monoclinic (t-m) phase transformation, and topographic surface analysis was performed by 3D profilometry, and data were analyzed using Mann-Witney test (p <0.05).Results: XRD measurements revealed no monoclinic phase in any of the abutments after aging. The comparative analysis regarding roughness (using the Sa parameter) at the abutments' seating platforms (using 3D profilometry) revealed a slight increase in roughness in both connections after TCML. Statistically significant differences (test U= 57.0, p = 0.161 > 0.05), before and after TCML, and between implants connections (test U= 57.0, p = 0.053 > 0.05) were not detected.Conclusions: After a 5-year simulation of its clinical use, the analyzed 3Y-TZP zirconia abutments did not show signs of aging. The connection's geometry does not interfere in aging.